2014
DOI: 10.1111/iwj.12261
|View full text |Cite
|
Sign up to set email alerts
|

The use of a surgical incision management system on vascular surgery incisions: a pilot study

Abstract: Health care-associated infections in hospitals, including surgical site infections, contribute significantly to morbidity as well as mortality. Surgical incision management (SIM) using negative pressure wound therapy (Prevena™ Incision Management System, Kinetic Concepts, Inc., San Antonio, TX, USA) is designed to cover and protect closed surgical incisions from external factors including infectious sources and local trauma, while negative pressure removes fluid and infectious material from the surgical incisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 2 publications
(1 reference statement)
0
24
1
Order By: Relevance
“…All three wound infections (6%) in the Matatov study were classified as Szilagyi grade I, while in this study, there were four incision complications classified as Szilagyi grade I and only one grade II. Similarly, the results of this study were consistent with the results of Weir (with only two incision complications) and Karl and Woeste (with no complications) after application of ciNPT. This observation supports the reduction of incision complications in deep tissue layers with possible revision surgeries when ciNPT is utilised.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…All three wound infections (6%) in the Matatov study were classified as Szilagyi grade I, while in this study, there were four incision complications classified as Szilagyi grade I and only one grade II. Similarly, the results of this study were consistent with the results of Weir (with only two incision complications) and Karl and Woeste (with no complications) after application of ciNPT. This observation supports the reduction of incision complications in deep tissue layers with possible revision surgeries when ciNPT is utilised.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of many publications, clinical studies involving groin wounds are rare. To date, there exist only four clinical studies in which ciNPT were examined on groin wounds after vascular surgeries (4,9,10,40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 These studies found that the use of incisional negative pressure therapy immediately after surgery decreased the number of SSIs, 12,13,16,17,19 overall wound complications, 13,15,17,27 seroma formation, 24,25 and complications requiring repeat surgery. 14,15,20 Also noted were reduced length of stay in hospital 18,27 and in intensive care unit, 20 reduced wound drainage, 21,[24][25][26] and time needed for dressing changes. 25,27 Finally, shortened time for drain removal 26 and increased ability to self-care 18 have also been identified.…”
mentioning
confidence: 99%